About Adam - Stembridge, Gerard; Frances O'Connor; Kate Hudson; Stewart Roche; Tommy Tiernan (Ireland USA UK British Broadcasting Corporation, 2000)
A waitress meets personable, attractive Adam and they soon become lovers, then get engaged. Wasting no time, Adam starts an affair with her bookish sister, who knows about the first relationship. Their (none-too-happily) married third sister knows about b
A waitress falls for a handsome customer who seduces her, her two sisters, her brother, and her brother's girlfriend.
He came. He saw. He conquered. One sister at a time.
Gerard Stembridge
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Comedy